The Effect of Autovalidation System Implementation in Laboratory Information System on Laboratory Result Validation Time - Yusuf Arimatea; I Gusti Putu Agus Ferry Sutrisna Putra; Ni Luh Gede Puspita Yanti (CV. CENDIKIA JENIUS INDONESIA, 2025)
Fast and accurate laboratory result validation is essential to support clinical services, yet manual processes often require considerable time and increase the risk of error. This study aimed to analyze the effect of implementing an autovalidation system within the Laboratory Information System (LIS) on laboratory result validation time at the Prodia National Reference Laboratory. This research employed a pre-experimental one group pretest-posttest design by analyzing 189,150 laboratory test records, consisting of 94,575 data from the pre-autovalidation period (2023) and 94,575 data from the post-autovalidation period (2024). Data were obtained from LIS integrated with the AlinIQ AMS Abbott Middleware. Descriptive analysis and the Wilcoxon Signed-Rank test were performed, as the data distribution was not normal. The findings revealed that the average validation time before autovalidation was 54.70 minutes, which decreased to 26.84 minutes after implementation. Time efficiency improved by 50.92%, while manual analyst involvement was reduced by 80.13%. Statistical analysis confirmed a significant difference (p < 0.001) between pre- and post-autovalidation periods. In conclusion, autovalidation implementation effectively accelerated validation time and reduced analyst workload, supporting the digital transformation of laboratories toward a more efficient and responsive system. It is recommended that other clinical laboratories adopt autovalidation while maintaining manual verification for results that fail system rules.